2013
DOI: 10.1016/j.jom.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sourcing enterprise system use and work process interdependence on sourcing professionals’ job outcomes

Abstract: a b s t r a c tWe examine sourcing professionals' work context to conceptualize how they use sourcing enterprise systems (SESs) and to understand when SES use results in positive/negative job outcomes. We differentiate between SES use for supplier selection and supplier governance, identify sourcing professionals' work process interdependence as a moderator for the impacts of SES use on job satisfaction, and suggest job satisfaction mediates the impacts of SES use on job performance. We conducted a field study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 72 publications
(119 reference statements)
2
19
0
Order By: Relevance
“…4–7). This advice aligns with research on factors that enhance and weaken the implementation effects of both ERP systems (Gattiker & Goodhue, ) and SEAs (Rai & Hornyak, ). Nonetheless, the literature does not answer whether using SEAs in appropriate conditions is truly more effective than using an ERP system, nor does it conclude which should be used when both differentiation and cross‐functional integration are needed simultaneously.…”
Section: Literature Reviewsupporting
confidence: 63%
See 3 more Smart Citations
“…4–7). This advice aligns with research on factors that enhance and weaken the implementation effects of both ERP systems (Gattiker & Goodhue, ) and SEAs (Rai & Hornyak, ). Nonetheless, the literature does not answer whether using SEAs in appropriate conditions is truly more effective than using an ERP system, nor does it conclude which should be used when both differentiation and cross‐functional integration are needed simultaneously.…”
Section: Literature Reviewsupporting
confidence: 63%
“…Research, moreover, has shown that the benefits of an ERP system increase along with the functional scope of its implementation (Ranganathan & Brown, ; Karimi et al., ). A number of studies, however, have documented the benefits of using enterprise software other than ERP systems, including business function‐specific software for sourcing (Rai & Hornyak, ), production planning (Banker, Bardhan, Hsihui, & Shu, ; Hendricks et al., ; Stratman, ; Carvalho, Scavarda, & Lustosa, ), sales (Sundaram, Schwarz, Jones, & Chin, ; Ahearne, Jones, Rapp, & Mathieu, ; Hsieh, Rai, Petter, & Ting, ; Zablah, Bellenger, Straub, & Johnston, ), and product design (Yassine, Kim, Roemer, & Holweg, ; Heim, Mallick, & Peng, ). Taken together, the available evidence presents three possible conclusions: (i) extensive use of both an ERP system and SEAs brings the maximum benefits, (ii) SEAs can replace an ERP system without adverse consequences to operational performance, or (iii) the relative effectiveness of an ERP system versus SEAs depends on the context.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…If in this case the allocation of indirect costs in the traditional way, it may cause the product cost distortion. Thus, the use of strategic cost management will be more than a single standard of distribution according to the cost drivers instead of the standard distribution, so as to highlight the advantages of management, in order to correctly calculate the cost of the product with the distribution of the indirect costs [4][5]. In this paper, we conduct research on the existing problems and countermeasures for enterprise cost management under modern enterprise system.…”
Section: Introductionmentioning
confidence: 99%